PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP MANAJEMEN LABA DALAM PERUSAHAAN TERDAFTAR DI INDONESIA: Studi Pada Perusahaan Non Keuangan Di Bursa Efek Indonesia Periode 2017- 2019 - Ericha Pricella, (2021)
The objective of this study is to examine the effect of the characteristics of the audit committee on earnings management at non-financial companies listed on the Indonesia Stock Exchange for the period 2017 - 2019. By using company size, leverage and profitability as control variables. Earnings management as the dependent variable is proxied by real earnings management (REM) measurements from Cohen et. al., (2008). The characteristics of the audit committee as an independent variable are proxied by the audit committee independent, audit committee expertise, and audit committee tenure. A sample of 516 listed Indonesian firms (non-financial) covering the period: 2017 to 2019 was used for the study. The analysis method used is linear regression analysis of panel data with random-effects model and STATA version 12.1. Based on the results of data analysis, it can be concluded that the audit committee independent and the audit committee expertise have no influence on earnings management, while the audit committee tenure has a positive and significant effect on earnings management.